The Value of Circulating Biomarkers in Bicuspid Aortic Valve-Associated Aortopathy - Naito, Shiho; Hillebrand, Mathias; Bernhardt, Alexander Martin Justus; Jagodzinski, Annika; Conradi, Lenard; Detter, Christian; Sydow, Karsten; Reichenspurner, Hermann; Kodolitsch, Yskert von; Girdauskas, Evaldas (The Thoracic and Cardiovascular Surgeon, 2018)
Traditional risk stratification model of bicuspid aortic valve (BAV) aortopathy is based on measurement of maximal cross-sectional aortic diameter, definition of proximal aortic shape, and aortic stiffness/elasticity parameters. However, conventional imaging-based criteria are unable to provide reliable information regarding the risk stratification in BAV aortopathy, especially considering the heterogeneous nature of BAV disease. Given those limitations of conventional imaging, there is a growing clinical interest to use circulating biomarkers in the screening process for thoracic aortic aneurysms as well as in the risk-assessment algorithms. We aimed to systematically review currently available biomarkers, which may be of value to predict the natural evolution of aortopathy in individuals with BAV.
Keywords: bicuspid aortic valve; aortopathy; biomarkers